Perlindungan Hukum Bagi Pekerja Harian Lepas Di PT.Rejeki Pinang Sukses Desa Sungai Gantang Kecamatan Kempas Kabupaten Indragiri Hilir - Mandasari; Wandi; Fitri Wahyuni (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2025)
The workforce is one of the spearheads as a supporting element of the government which has a very important role for the success of development so that policies in the field of employment in the national development program are always attempted to create as many job opportunities as possible in various business fields which are balanced with increasing quality and increasing protection for the workforce. Based on this study, the following problem formulation can be taken. How is the legal protection for casual daily workers at PT Pinang Sukses, Sungai Gantang Village, Kempas District and What are the inhibiting factors and efforts for legal protection for casual daily workers at PT Pinang Sukses, Sungai Gantang Village, Kempas District.